Valorization of Olive Mill Wastewater by Selective Sequential Fermentation - Lara Signorello; Mattia Pia Arena; Marcello Brugnoli; Flora V. Romeo; Maria Gullo (Foods)
Olive mill wastewater is a by-product of olive oil extraction, characterized by a high concentration of organic matter, which presents a significant environmental challenge if not properly managed. This study was aimed at valorizing olive mill wastewater through selective fermentations to produce acetic beverages with low or no alcohol content. Olive mill wastewaters at three different dilutions (100%, 75% and 50%) were inoculated with Saccharomyces cerevisiae UMCC 855 for alcoholic fermentation. The resulting alcoholic product, with 75% olive mill wastewater, was then used as a substrate for acetic acid fermentation by Acetobacter pasteurianus UMCC 1754, employing both static and submerged acetification systems. The results showed that, at the end of the static acetification process, no residual ethanol was detected and that high concentrations of acetic and gluconic acid (46.85 and 44.87 g/L, respectively) were observed. In the submerged fermentation system, the final ethanol concentration was 24.74 g/L; the produced organic acids content reached 31.63 g/L of acetic acid and 39.90 g/L of gluconic acid. Furthermore, chemical analyses revealed that fermentation enhanced the antioxidant activity of olive mill wastewater. These results suggest promising insights for the valorization of olive mill wastewater.